STATUS OF HEMOLYMPHOCIRKULATION DURING EXACERBATION OF CHRONIC INFLAMMATORY OF WOMEN SMALL PELVIC ORGANS AND DUKING OF THEIR CORRECTION - O. G. Pekarev; M. S. Lyubarskiy; T. V. Ovsyannikova; E. O. Pekarevа (Акушерство, гинекология и репродукция, 2016)
Purpose: it was concluded in revealing the particularities hemolymphocirculation in pool of the small pelvic at exacerbation of the chronic inflammation beside woman's and study efficiency to their correction with use lymphogenic technology. Define clinical and morphological criteria of scar after caesarean section to form the groups pregnant for the following vaginal labor. Methodology: prospective study. Subjects: 314 women with chronic pelvic inflammatory disease in stage of the intensification. Methods: reolymphovasography for quantitative and qualitative estimation of the factors lymphodinamic on 1, 5 and 7 day of the treatment. Teplovizion study by means of teplovizor IFP-M in mode of the real time. The range of the temperature 25-41оС, limiting sensitivity of the instrument not less 0,1оС. The scene of the heat relief registered in projections pelvic organ in hypogastric`s area. Results: Under chronic inflammation organ small basin in stage of the intensification occurred the reduction of the arterial influx in region of the small basin in 2-6 once, increase venous and lymphatic current in 1,5-3 times, increasing of the kinetic resistance in arterial riverbed and reduction in venous-lymphatic section, as well as reduction in 1,3-3,5 times. Herewith time of the filling microcirculation and venous riverbed. Use lymphogenic technology in correction of the chronic pelvic inflammatory disease brought about increase the arterial influx in small basin on 23%, time of the microcirculatory and venous division on 36%, initial and final velocity of the influx in 1,4 times, velocities and volume venous and lymphatic filling on 13-14%. When change the cofrom-carryings arterial, venous and lymphatic section approached to factor beside «practically normal» women. The offered diagnostic criteria degrees to insufficiency hemolymphocirculation in pool of the small basin under chronic inflammation in stage of the intensification beside women, as new on given reolymphovasography and remote teplovizion studies have allowed to value the condition an hemolymphocirculation in region. Conclusion: Marketed in persisting work approach to treatment of the chronic pelvic inflammatory diseases with use of lymphogenic technology has shown pathogenetic directivity of the applying methods and, as effect, this high clinical efficiency, and as a result of reduction inflammatory process when recovering hemolymphocirculation in region of the small pelvic. The method of reolymphovasography for op-remissions of the breaches hemolymphocirculation in pool of the small basin is criterion to efficiency treatments chronic pelvic inflammatory disease